HUBUNGAN STATUS GIZI DENGAN KEMAMPUAN MOTORIK SISWA-SISWI KELAS ATAS SD NEGERI 19 TANJUNG KUDA KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Huvat, Albuinuslinus; Supriatna, Eka; Yanti, Novi; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the relationship between nutritional status and motor skills of upper grade students at SD Negeri 19 Tanjung Kuda, North Putussibau District, Kapuas Hulu District. The method used in this study is a quantitative method with a correlational approach. The population and sample in this study amounted to 47 people. The analysis technique used is to look for regression and then look for the correlation of each variable by comparing the f-table with a significant level of 0.05. The results showed that there was a significant relationship between nutritional status (x) and motor skills (y). the result of the correlation coefficient is 0.874 because the significance of the variable x and variable y is 0.05, so it is correlated. The Pearson correlation value of the two variables is 0.874, so the degree of relationship is perfect and positive correlation. From the discussion it can be concluded that there is a positive and significant relationship between nutritional status and motor skills of the upper grade students of SD Negeri 19 Tanjung Kuda, North Putussibau District, Kapuas Hulu Regency.